The influence of weather conditions on breeding dates of the common gull (Larus canus) in the south of Western Siberia - M. Yu. Garyushkina; A. K. Yurlov (Юг России: экология, развитие)
Aim. The purpose of this research was to find out what local weather factors influence the nesting timing of the common gull (Larus canus). Material and Methods. The time of egg laying by the common gull was determined using data obtained during regular surveys over 8 years (1996‐1998, 2002‐2003, 2006‐2008) on the islands of Lake Bolshie Chany. Weather and climatic factors were assessed using open‐access databases. Results. It was been established that the start of egg‐laying in the colony of the common gull is determined by wind strength, the number of rainy days, the associated atmospheric pressure during the second decade of April, and the air temperature – the transition date at which the average daily air temperature rose above 0°C. In years with unstable spring temperatures, a relationship was revealed between the air temperature and the intensity of egg laying by the common gulls by day. In years when temperatures rise evenly, precipitation and wind speed become the main factors.Conclusion. We conclude that the egg‐laying dates of the common gull is influenced by weather variables during the whole nesting season and not predominantly by early season variables. We also show the importance of large‐scale climatic phenomena such as the EAWR in explaining variability in timing of the nesting of the common gull in Siberia. We suggest that future studies should focus on the effects of extremes in weather variables and global climatic phenomena.